2022
DOI: 10.3390/ma15134540
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nisin-Loaded Poly(ε-caprolactone)-Based Active Food Packaging

Abstract: Packaging for fresh fruits and vegetables with additional properties such as inhibition of pathogens grown can reduce food waste. With its biodegradability, poly(ε-caprolactone) (PCL) is a good candidate for packaging material, especially in the form of an electrospun membrane. The preparation of nonwoven fabric of PCL loaded with food additive, antimicrobial nisin makes them an active packaging with antispoilage properties. During the investigation of the nonwoven fabric mats, different concentrations of nisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The high porosity of the materials obtained facilitated the permeability of the gases (CO 2, O 2 ), which is highly desired from an economic and environmental protection point of view because the amount of material used for preparation is much lower than that used in traditional methods. Packages made of PCL and PCL/nisin fibrous mats demonstrated antispoilage properties that result in a prolonged freshness of fruits, improving their shelf life and, consequently, their safety [ 489 ].…”
Section: Application Of Biodegradable Polymers and Antibacterial Poly...mentioning
confidence: 99%
“…The high porosity of the materials obtained facilitated the permeability of the gases (CO 2, O 2 ), which is highly desired from an economic and environmental protection point of view because the amount of material used for preparation is much lower than that used in traditional methods. Packages made of PCL and PCL/nisin fibrous mats demonstrated antispoilage properties that result in a prolonged freshness of fruits, improving their shelf life and, consequently, their safety [ 489 ].…”
Section: Application Of Biodegradable Polymers and Antibacterial Poly...mentioning
confidence: 99%
“…Electrospun fibers loaded with functional substances such as absorbents, hazardous substance scavengers, and antibacterial antioxidants are used as active food packaging to prevent biological, chemical, and physical hazards brought by the external environment of food and achieve the function of stabilizing and maintaining the quality of food itself 17 . As shown in Figure 4a and Figure 4b, Siskova et al extended the fresh-keeping time of tomatoes and kiwifruit by electrospinning nanofibers prepared by loading nisin with polycaprolactone 18 . Figure 4c shows that the PEO/zein nanofiber containing resveratrol and nanosilver prepared by Jiang et al extended the fresh-keeping period of cherry tomato 19 .…”
Section: Application Statusmentioning
confidence: 99%
“…Therefore, different nisin concentrations were introduced into a poly(ε-caprolactone) (PCL) solution to obtain active packaging with antibacterial activity against Escherichia coli and Staphylococcus aureus . It was reported that the addition of nisin lead to increased tensile strength, together with the decrease in elongation at break, explained by the action of nisin particles as a bulky barrier to reducing the macromolecular chains movement of PCL [ 61 ]. The same finding was observed by Yang et al (2020) [ 53 ], when increasing the concentration of nisin at 0, 640, 1280, 1920, 2560, and 3200 mg/L into cellulose nanofibrils (CNFs) prepared from sugarcane bagasse.…”
Section: Background Theorymentioning
confidence: 99%